2012
DOI: 10.1159/000171029
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Tryptase Induces Microglia Activation via Protease-activated Receptor 2 Signaling

Abstract: Background: Mast cell tryptase can stimulate peripheral mononuclear cells activation to cause widespread inflammation. However, the influence of tryptase on microglia, the resident immune cells in the brain, remains uninvestigated. Since microglia plays a pivotal role in immune surveillance of CNS, we studied the effect of tryptase on microglia activation. Methods: Induction of microglia activation by tryptase was examined with primary cultured microglia. TNF-alpha and IL-6 was measured with a commercial ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 47 publications
4
86
0
Order By: Relevance
“…Microglia-derived IL-1β, CXCL8, CCL2, and CCL5 in response to NT can augment the activation of perivascular mast cells, further disrupting the BBB (82-84), perhaps initiating a feedback mechanism. Microglia are stimulated by mast cellderived histamine (85) and tryptase (86). Hence, communication 6 cells) were stimulated with NT (10 nM) for 0-60 min.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia-derived IL-1β, CXCL8, CCL2, and CCL5 in response to NT can augment the activation of perivascular mast cells, further disrupting the BBB (82-84), perhaps initiating a feedback mechanism. Microglia are stimulated by mast cellderived histamine (85) and tryptase (86). Hence, communication 6 cells) were stimulated with NT (10 nM) for 0-60 min.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, mast cell tryptase can activate microglia via PAR2 and PAR2 expression on mast cells can be increased by tumour necrosis factor (Zhang et al, 2010;Zhang et al, 2012). There were very low numbers of mast cells in the brain regions examined in this study.…”
Section: Mast Cellsmentioning
confidence: 54%
“…MCs produce a vast array of mediators, including proteases and vasoactive amines such as GnRH [13] and histamine [14]. MCs were reported to induce microglial activation and inflammatory mediator release in our previous studies [15,16], suggesting the pivotal role of MCs in the induction of CNS inflammation. These neuromodulators released by MCs result in a variety of inflammatory diseases affected by stress [17].…”
Section: Introductionmentioning
confidence: 95%
“…Yuan reported that mast cell activation induced microglia to release neurotrophin [20]. We previously reported that tryptase and histamine, which are mediators released from MCs, induced microglial activation and inflammatory mediator release [15,16]. However, the effect of MCs on microglial activation is unclear.…”
Section: Introductionmentioning
confidence: 99%